Analisis Daya Saing Ekspor Kayu Manis Indonesia Terhadap Lima Negara Tujuan Ekspor - Sihombing, Vista Uli; Siregar, Futri Medwina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Cinnamon is one of Indonesia's leading spice commodities with great international trade potential. Indonesia is known as one of the world's major producers and exporters of cinnamon, with export destination countries such as the United States, France, the Netherlands, Thailand and Malaysia. However, the competitiveness of Indonesian cinnamon exports experiences different dynamics in each destination country. This study aims to analyze the competitiveness of Indonesian cinnamon exports to the five destination countries using two approaches, namely the Index of Trade Specialization (ISP) and Revealed Comparative Advantage (RCA). The data used is secondary data taken from TradeMap and UN Comtraded in the form of export and import values of Indonesian and world cinnamon from 2015-2024 and analyzed quantitatively. The results showed that Indonesia's ISP value was consistently in the positive range (0-1), which indicated that Indonesia was an exporter of cinnamon even though it had the lowest index in 2021. Meanwhile, the RCA value against five export destination countries shows that Indonesian cinnamon has a comparative advantage, with the highest RCA value in France at an average of 233,73 and the lowest in Malaysia at an average of 11,62. These findings indicate that Indonesia's cinnamon competitiveness position is still strong but requires a market differentiation and diversification strategy to reduce dependence on specific countries and be able to face increasingly complex global competition.